2010
DOI: 10.1186/1471-244x-10-63
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age of onset on clinical characteristics in schizophrenia spectrum disorders

Abstract: BackgroundOver the last few decades, research regarding the age of onset of schizophrenia and its relationship with other clinical variables has been incorporated into clinical practices. However, reports of potential differences in demographic and clinical characteristics between early- and adult-onset schizophrenia spectrum disorders have been controversial. Thus, this study aims to assess differences in demographic and clinical characteristics correlated with age of illness onset in schizophrenia spectrum d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
41
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 52 publications
4
41
2
2
Order By: Relevance
“…By comparison, Oie et al [74] found a mean GAS score of 47.7 in their EOS group containing 15 patients assessed when they were clinically stable on antipsychotic medication and followed up for 13 years. Moreover, Kao et al [75] found a mean GAF score of 47 in 19 EOS patients after 1 year follow-up, and Gochman et al [76] found a mean CGAS score of 43.6 after at least 8 years of follow-up. In the single intervention study included in the current review, the mean GAF score was 35 in the intervention group and 24 in the control group [55].…”
Section: Discussionmentioning
confidence: 99%
“…By comparison, Oie et al [74] found a mean GAS score of 47.7 in their EOS group containing 15 patients assessed when they were clinically stable on antipsychotic medication and followed up for 13 years. Moreover, Kao et al [75] found a mean GAF score of 47 in 19 EOS patients after 1 year follow-up, and Gochman et al [76] found a mean CGAS score of 43.6 after at least 8 years of follow-up. In the single intervention study included in the current review, the mean GAF score was 35 in the intervention group and 24 in the control group [55].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier onset age was associated with a higher severity of idiosyncratic disturbances, which is consistent with a large body of evidence linking early onset to an overall more severe form of psychosis, including higher levels of TD (Kao et al, 2010). Interestingly, earlier onset has been found to characterize familial psychosis, a finding that was replicated in the current data (Husted, Greenwood, & Bassett, 2006;Kendler & MacLean, 1990).…”
Section: Summary Of Resultssupporting
confidence: 89%
“…En varios estudios se ha reportado que las mujeres presentan inicio más tardío y menor gravedad de la enfermedad (6)(7)(8)(9). Además, en hombres se ha encontrado un peor funcionamiento premórbido, más síntomas negativos y cognoscitivos, así como una mayor frecuencia de anormalidades cerebrales estructurales o trastornos neuropsicológicos (10).…”
unclassified